Perkembangan Perpajakan di Indonesia - Prakasa, Tyas Zakiya; Isfaatun, Eliya (Kajian Ekonomi dan Bisnis, 2020)
This study aims to determine the development of taxation in Indonesia in 2012-2017 with variable trends in tax revenue, the number of taxpayers, tax compliance, tax return reporting with e-filing, and the performance of the Directorate General of Taxes. This research is a descriptive analysis research. The type of data used is secondary data with the object of this study is the annual report and the performance report of the Directorate General of Taxes. The research data collection technique is the documentation technique. Based on the analysis that has been done, there is a correlation between the variable trend of tax revenue, the number of taxpayers, taxpayer compliance, SPT reporting with e-filing, and the performance of the Directorate General of Taxes with the development of taxation in Indonesia during 2012-2017. With the conclusion, the trend of tax revenue increases, the number of mandatory increases, the ratio of taxpayer compliance increases, the reporting of tax returns with increasing e-filing and the performance of the Directorate General of Taxes has increased every year